Perancangan Sistem Parkir Cerdas U-Park Berbasis QR Code dengan Autentikasi Ktm dan Akses Web di Lingkungan Kampus UPN “Veteran” Jawa Timur - Abdul Aziz, Muhammad; Pranatalie Krispyanto, Steffanuel; Satria Kirana, Tegar; Afriza, Surya (Prosiding Seminar Nasional Informatika Bela Negara (SANTIKA), 2025)
Parking management on campus is an important part of campus facility management, especially in the midst of increasing student numbers. At the National Development University "Veteran" of East Java (UPNVJT), the manual parking system causes problems in terms of efficiency, security, and activity recording. This research designs a QR Code-based parking system that is integrated with the Student Identity Card (KTM). The Design Thinking approach is used to formulate solutions based on user needs. The designed system replaces the role of STNK as a verification tool by utilizing the unique QR Code on KTM. The design process involves problem identification, prototyping, and testing of parking lot entry and exit. The results of the testing show that the system can improve the efficiency and security of parking access. This concept is expected to be implemented as an innovative solution to parking problems on the UPNVJT campus.